(untitled) (Medico Legal Update, 2021)
Objectives: To assess the knowledge of patients with acute renal failure concerning dietary pattern for kidney failure in dialysis unite in AL-Zahraa Teaching Hospital at AL-Kut City and Find out relationship between demographic data and knowledge of patient with acute kidney failure. By a non- probability sample account of (30) subjects is selected for the purpose of the present study. A questionnaire as aincomes for data gathering, it consist of two parts; include demographic data and knowledge of patients with acute renal failure concerning dietary pattern which composed of (18) items. By self-administration, data are collected from those who patients with renal failure come in dialysis unite in AL-Zahraa Teaching Hospital and analyzed through the used descriptive and inferential statistic approach. The study results indicated that the most of the participants are within married (60%), and most of them are male. In regarding level of education, they most of them formally graduation, and administrative patients, as well the subjects have chronic disease such as diabetes mellitus and find statistical high significant between level of education and knowledge of patient at p-value <0.05 with non-significant between other demographical data